IMPLEMENTASI MODERASI BERAGAMA PADA PEMBELAJARAN AL-QUR’AN DI MUSHOLA NUR AHMAD - Zahdi, Zahdi; Iqrima, Iqrima (Moderatio: Jurnal Moderasi Beragama, 2021)
Being a country with the most Muslim population makes Indonesia a country with many mosques as places of worship. Which then gave rise to many Al-Qur'an Reading Gardens that stood in every mosque. One of the functions of the mosque is a means of education, both formal and non-formal. Since the time of the Prophet Muhammad, the mosque has not only functioned as a place of worship. The mosque functioned as a meeting room to gain knowledge and wisdom from the Prophet Muhammad. It is narrated that at the time of the Prophet Muhammad, the Prophet's Mosque, apart from being used as a place of worship, also functioned for the companions of the Prophet who did not have a place to live. Therefore, in this case, how is religious moderation in Arrohim Mosque and its application to TPQ children and the surrounding community? This is the main problem in this research whose answers can be found through a qualitative approach. For the purpose of collecting accurate data, researchers used interviews and direct observation techniques conducted at the Arrohim Mosque, Nampirejo Village, Batanghari District, East Lampung Regency. This study reveals several things, including that religious moderation in the Arrohim Mosque is going well and the existence of the mosque is able to raise the enthusiasm of the community and also the surrounding children to worship and get closer to the Almighty and to be more enthusiastic in learning Islam